2021
DOI: 10.1016/j.jds.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a bioadhesive barrier-forming oral liquid on pain due to radiation-induced oral mucositis in patients with head and neck cancer: A randomized crossover, preliminary study

Abstract: Background/purpose Bioadhesive barrier-forming oral liquid, is a recently developed medical material for the management of pain caused by oral mucositis associated with cancer radiotherapy or chemotherapy. The purpose of this study was to evaluate the effectiveness of this liquid in relieving pain resulting from radiation-induced oral mucositis in patients with head and neck cancer. Materials and methods This randomized, crossover trial investigated the analgesic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Pueden utilizarse agentes tópicos o sistémicos, los cuales están disponibles en diversas presentaciones. Un estudio realizado en pacientes con RIOM comparó el efecto de un líquido oral (Episil), formador de barrera cristalina bioadhesiva superficial que protege a la mucosa, con la pomada de dexametasona para mitigar el dolor relacionado a la mucositis oral y encontró que el Episil alivió el dolor en un 71,4% y la pomada de dexametasona en un 85,7% de los pacientes 30 . Rasic et al 31 administraron localmente un spray compuesto por lisozima, cetilpiridinio y lidocaína en pacientes con RIOM y encontraron que fue eficaz al disminuir los signos de inflamación y la intensidad del dolor al comer y hablar.…”
Section: Manejo Terapéutico Para La Mucositis Oralunclassified
“…Pueden utilizarse agentes tópicos o sistémicos, los cuales están disponibles en diversas presentaciones. Un estudio realizado en pacientes con RIOM comparó el efecto de un líquido oral (Episil), formador de barrera cristalina bioadhesiva superficial que protege a la mucosa, con la pomada de dexametasona para mitigar el dolor relacionado a la mucositis oral y encontró que el Episil alivió el dolor en un 71,4% y la pomada de dexametasona en un 85,7% de los pacientes 30 . Rasic et al 31 administraron localmente un spray compuesto por lisozima, cetilpiridinio y lidocaína en pacientes con RIOM y encontraron que fue eficaz al disminuir los signos de inflamación y la intensidad del dolor al comer y hablar.…”
Section: Manejo Terapéutico Para La Mucositis Oralunclassified
“…Ueno T et al used Episil® in ten Japanese cancer patients and clearly demonstrated its pain-relieving effect on OM [ 12 ], however, only one RT with HNC patient was included, the effects of Episil® in patients with HNC, remain unclear. Moreover, adverse reactions to Episil® have been observed, including nausea and difficulties experienced in the proper application at the OM site [ 13 ]. Clinically, we have observed both benefits and difficulties when using Episil® in patients with HNC; however, these experiences have been rarely discussed in the literature and thus, more evidence is needed to support the use of Episil® in patients with HNC.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that Episil® is an effective and safe product for pain relief caused by OM in patients with cancer [8,12]. However, adverse reactions of Episil® have been noted, including nausea and di culties in proper application at the OM site [13].…”
Section: Introductionmentioning
confidence: 99%